The Influence of Using Canva Media on Science Learning Outcomes in Class V of SDN 3 Rempek in the 2023/2024 Academic Year - Abandi, Nobi; Hadi, Rusman; Mulyono, Ana (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research aims to determine the effect of Canva media on science and science cognitive learning outcomes in food chain material in class V at SDN 3 Rempek. This research was carried out at SDN 3 Rempek on class V students of SDN 3 Rempek for the 2023/2024 academic year with a population of 14 students. Sampling was carried out using a saturated sampling technique. The total sample of 14 students was used as one experimental class. This research is pre-experimental research with a One Group Pretest-Posttest Design. Data collection techniques are observation, interviews, documentation and learning outcomes tests. Data collected through science and science cognitive learning results were tested for normality, homogeneity and hypothesis testing, t-test (paired sample T-test). The results of this research are: there is an influence of Canva media on cognitive science learning outcomes in food chain material in class V SDN 3 Rempek based on the results of data analysis, the average pretest score is 64.28 from 14 students with a KKM of 70, that is, there are 9 who got a score of 45-65. students can be categorized as low while scores of 70-85 are 5 students who can be categorized as high scores. Based on the posttest results after applying Canva media, the average is 75.35. From the score of 60-65 consisting of 3 students, it can be said to be a low score, while the score of 70-90 consists of 11 students, it is said to be the highest score. The difference between the pretest and posttest scores is 11. 07 then the posttest score is higher than the pretest. The results of hypothesis testing with the T-test (Paired Sample t-Test) have a 2-tailed sig value of 0.000<0.05, so it can be stated that there is a real difference between the science and science cognitive learning results for food chain material in the pretest value and the posttest value. The results of calculating the T-table using T-count are -4.954>1.782 with a significance level of 0.05. It can be stated that Ha is accepted and Ho is rejected. The application of the Canva media has an influence on the science learning outcomes of food chain material. So, the application of Canva media can have a significant influence on the cognitive learning outcomes of science and science on food chain material in class V SDN 3 Rempek so that Canva media provides interest, interest, motivation, learning outcomes, focus, concentration and understanding of the concept of the material.